2022
DOI: 10.1002/term.3351
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth analysis of the relationship between bovine intestinal organoids and enteroids based on morphology and transcriptome

Abstract: Intestinal organoids and enteroids as excellent models are miniaturized and simplified for studying intestinal physiological and pathological functions, drug screening, and regenerative medicine. Recently, the application demands for organoids and enteroids in organ development and nutrition metabolism, immune and cancer research increased. But there are few comparative studies on both of them, especially in immunity and metabolism, which is also conducive to further clarifying the role of crypt stem cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…As a limitation, the present study did not evaluate the direct gene expression of the donor tissue; thus, it is not possible to compare and discuss similarities or diferences in genetic properties between the organoids and their originating tissues. However, previous studies reported an overlapping gene expression pattern between bovine intestinal organoids and the in vivo tissue [15,16,44]. Tis characteristic has also been reported for other types of organoids such as the human and murine liver [45,46].…”
Section: Discussionmentioning
confidence: 78%
“…As a limitation, the present study did not evaluate the direct gene expression of the donor tissue; thus, it is not possible to compare and discuss similarities or diferences in genetic properties between the organoids and their originating tissues. However, previous studies reported an overlapping gene expression pattern between bovine intestinal organoids and the in vivo tissue [15,16,44]. Tis characteristic has also been reported for other types of organoids such as the human and murine liver [45,46].…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, several formulations ( Table S1 ) for the manipulation of growth factors and differentiation of the enteroids were tested, but our results did not indicate that modifying the concentration of growth factors mentioned above was necessary for differentiation. Embedding the enteroids in Matrigel could also have contributed to differentiation, as described by [ 51 , 52 ]. To lower any Matrigel-driven differentiation, we used Matrigel with reduced growth factors [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protocols for culturing ruminant organoids from different digestive segments have been set out in [112][113][114][115][116][117][118][119][120]. Since the first report in 2009, intestinal organoids have evolved as a potential alternative to in vivo models for various experimental purposes, such as imaging, molecular analysis and gene editing, but also as reductionist approaches with which to study the interaction of epithelial cells with the other relevant actors in a physiological context, such as the immune cells [121,122] or microbiota [123,124], or even to evaluate the early host-pathogen interaction in the context of many infectious diseases (protozoa [125,126], virus [127], and bacteria [128][129][130][131][132][133]).…”
Section: Organoidsmentioning
confidence: 99%